Application of neuro-fuzzy models to grinding wheel parameters (2010)
Grinding is one of the most important finishing operations and it is very useful in our automobile industries. A grinding wheel is made of very small, sharp and hard abrasive particles or grits held together by strong porous bond. The paper presents, a control system for grinding process using neuro-fuzzy technique. The grinding parameters include circumferential speed of a grinding segment workpiece velocity and work depth of cut. The maximum grinding temperature is very important since too high temperature will lead to surface burns and thermal damage to the grinding wheel as well as the workpiece material. For fuzzy modeling, all the numerical values are replaced with linguistic values. The research work can be applied to any other grinding process, whether it is a wet or dry grinding process.